An Overview and Management of Painful Menstrual Disorder (Dysmenorrhea): A Narrative Literature Review - Juntu, Petrus; Ananta, Gede (Sriwijaya Journal of Obstetrics and Gynecology, 2023)
Primary dysmen orrhea is menstrual pain associated with the release of prostaglandins in the ovulatory cycle, but not with the pelvic disease. Approximately 9 0% of all women experience dysmenorrhea, 15% of whom are unable to last 1 to 3 days because of the severity of the pain. This literature review aimed to describe an overview and management of dysmenorrhea. Primary dysmenorrhea usually begins with the onset of ovulation cycles, with the highest prevalence in adolescence. In contrast, secondary dysme norrhea is associated with pelvic pathology (i.e., ovarian cysts, adenomyosis, endometriosis) that manifests in later reproductive years and can oc cur at any point in the menstrual cycle. Administration of nonsteroidal ant i-inflammatory drugs (NSAIDs) is the treatment of choice because these drugs reduce the activity of the cyclooxygenase (COX) enzyme and, thus, the p roduction of prostaglandins. NSAIDs work in the majority of women with primary dysmenorrhea and are most effective when started at the first sign of b leeding or cramping.